Hubungan Filsafat dengan Ilmu Pengetahuan dan Relevansinya Di Era Revolusi Industri 4.0 (Society 5.0) - Muhammad Rijal Fadli (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2021)
Philosophy and science are human efforts in understanding the concepts and methods of a scientific discipline. The changing times and developments have ushered the philosophy of a configuration by showing how the